2021
DOI: 10.1590/1980-57642021dn15-010005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive intervention on cognitive symptoms and quality of life in idiopathic Parkinson’s disease: a randomized and controlled study

Abstract: ABSTRACT. Pharmacological treatments for mild cognitive impairment (MCI), are lacking, and alternative approaches have been implemented, including cognitive training (CT). Objective: To determine the impact of CT on cognitive and quality of life measures in patients with Parkinson’s disease (PD) who were seen a hospital neurorehabilitation program. Methods: Thirty-nine individuals with MCI-PD, according to the Movement Disorder Society, were randomly distributed into two groups: experimental and control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…33,35 Considering that the PD patient may show impairment in several vital aspects such as feeding, communication, and locomotion, understanding their perception of QoL is essential to improve the daily living activities. 5,7,8,19 It was observed that as PD progresses and its symptoms become more evident, the scores of the PDQ-39 also increase and QoL tends to get worse. Interestingly, differences in the scores of mobility and activities of daily living domains are the aspects that impact the individuals QoL the most, probably due to the disease progress and its most evident symptoms: bradykinesia, rigidity, postural instability, and resting tremor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…33,35 Considering that the PD patient may show impairment in several vital aspects such as feeding, communication, and locomotion, understanding their perception of QoL is essential to improve the daily living activities. 5,7,8,19 It was observed that as PD progresses and its symptoms become more evident, the scores of the PDQ-39 also increase and QoL tends to get worse. Interestingly, differences in the scores of mobility and activities of daily living domains are the aspects that impact the individuals QoL the most, probably due to the disease progress and its most evident symptoms: bradykinesia, rigidity, postural instability, and resting tremor.…”
Section: Discussionmentioning
confidence: 99%
“…The validated version of the Parkinson's Disease Questionnaire (PDQ-39) 8 was applied to PG with the aim of assessing their overall quality of life; it comprises 39 questions that measure eight health domains in PD: functional mobility, activities of daily living, emotional well-being, stigma, social support, cognition, communication, and bodily discomfort. The score for each question ranges from zero (0) to four ( 4).…”
Section: Clinical Assessment and Questionnairesmentioning
confidence: 99%
See 3 more Smart Citations